Concentration-dependent effects of boron fertilizer on growth, yield, and quality of buckwheat - Jiang, Ying; Wang, Sunyu; Liu, Yanmin; Wang, An; Chang, Lei; Cai, Yingchun; Yu, Tian; Chang, QingTao (Frontiers in Plant Science, 2025)
IntroductionBoron is an essential trace element for plant growth and development, playing a critical role in flowering, fruit setting, nutrient transport, and stress resistance in crops. Buckwheat is‌ an important coarse grain crop, ‌and‌ its yield and quality are easily affected by boron nutritional status.MethodsIn order to identify the optimal concentration of boron fertilizer to maximize growth and yield of buckwheat, pot experiments and field trials were carried out at different mass concentrations of boron fertilizer solution: 0, 12, 24, 48, and 72 mg/L.ResultsThe results showed that 48 mg/L boron fertilizer solution promoted seed germination and seedling growth of Suqiao 1, whereas 24 mg/L boron fertilizer solution had the best effect on seed germination and seedling growth of 1412-69. Moreover, the levels of activity of superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) of Suqiao 1 seedlings were highest under the 48 mg/L boron fertilizer treatment, and those in 1412–69 were highest under the 24 mg/L treatment. The highest grain yield and grain quality of Suqiao 1 were found at a boron concentration of 48 mg/L, whereas grain yield and quality of 1412–69 were maximized at a concentration of 24 mg/L.DiscussionIn summary, boron fertilizer solutions at optimal concentrations can effectively stimulate buckwheat seed germination and seedling growth and thus enhance buckwheat yield.